THE IMPLEMENTATION OF CHARACTER EDUCATION STRENGTHENING PROGRAM (PPK) IN THE NEW ADAPTATION ERA IN CIVIC EDUCATION LEARNING (DESCRIPTIVE STUDY AT SMP NEGERI 1 RANGKASBITUNG) - Amanda Salsa Nabila; Wika Hardika Legiani; Dinar Sugiana Fitrayadi (Institut Pendidikan Indonesia, 2023)
This research is motivated by problems in student attitudes and behavior since the Covid-19 pandemic. These problems can be overcome by implementing penguatan pendidikan karakter programs. Therefore, the purpose of this study was to determine the implementation Penguatan Pendidikan Karakter (PPK) program carried out by SMPN 1 Rangkasbitung, reviewed by several programs and strategies for Penguatan Pendidikan Karakter (PPK) that were implemented so as to enable character strengthening in students. This research was conducted at SMPN 1 Rangkasbitung 1 in the 2022/2023 academic year. As for when the research began in March 2023. The research method used is a qualitative method with a descriptive study. This study uses data collection techniques of observation, interviews, and documentation. The data analysis technique used in this research is data reduction, data display, and data verification. The sampling technique used is the snowball sampling technique. The results showed that the implementation of the Character Education Strengthening (PPK) program which was carried out at SMP Negeri 1 Rangkasbitung was through habituation, intra-curricular programs and integrated into Teaching and Learning Activities (KBM). Through this habituation, the character values that have been developed in Civics learning, especially in SMP Negeri 1 Rangkasbitung, are in accordance with the five main characters that are the priorities for the development of the Character Education Strengthening (PPK) movement, namely religious, nationalist, integrity, independence, and mutual cooperation.